2022
DOI: 10.1093/lifemedi/lnac014
|View full text |Cite
|
Sign up to set email alerts
|

Aging-associated accumulation of mitochondrial DNA mutations in tumor origin

Abstract: The majority of cancer patients are among aged population, suggesting an urgent need to advance our knowledge on complicated relationship between aging and cancer. It has been hypothesized that metabolic changes during aging could act as a driver for tumorigenesis. Given the fact that mitochondrial DNA (mtDNA) mutations are common in both tumors and aged tissues, it is interesting to contemplate possible role of age-related mtDNA mutations in tumorigenesis. MtDNA encodes genes essential for mitochondrial metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 197 publications
1
13
0
Order By: Relevance
“…2C and 2D ). Consistent with a previous study suggesting that a dysfunctional electron transport chain may lead to ROS accumulation ( Chen et al , 2003 ; Kong et al , 2022 ), we observed increased mitochondrial ROS and cellular H 2 O 2 levels in EIF4EBP1 −/− hMSCs ( Fig. 2E–H ).…”
Section: Resultssupporting
confidence: 92%
“…2C and 2D ). Consistent with a previous study suggesting that a dysfunctional electron transport chain may lead to ROS accumulation ( Chen et al , 2003 ; Kong et al , 2022 ), we observed increased mitochondrial ROS and cellular H 2 O 2 levels in EIF4EBP1 −/− hMSCs ( Fig. 2E–H ).…”
Section: Resultssupporting
confidence: 92%
“…The accumulation of mtDNA mutations has been considered to be an important contributor to aging and age-related diseases (Kong et al, 2022;Larsson, 2010;Linnane et al, 1989;Payne and Chinnery, 2015). mtDNA mutations have been reported to induce the aging of multiple organs in mice, such as the ovary, heart, and liver (Giorgi et al, 2018;Kauppila et al, 2017;Kujoth et al, 2005;Niemann et al, 2017;Trifunovic et al, 2004;Yang et al, 2020;Zhang et al, 2018a).…”
Section: Mtdna Mutationsmentioning
confidence: 99%
“…Therefore, we suspected that such excessive cytoplasmic DNA might be recognized by the DNA sensor cGMP-AMP synthase (cGAS) and trigger activation of the innate immune system (Figure 4B). [48][49][50] Indeed, by immunoprecipitation analysis, we verified the marked enrichment of cGAS on cytoplasmic HERVK DNA in senescent hMPCs, which was not the case in early-passage young hMPCs (Figure 4C). Supporting cytosolic HERVK DNA triggering activation of the cGAS-Stimulator of interferon genes (STING) pathway, we detected increases in 2'3'-cGAMP content (Figure 4D), and phosphorylation of TANK-binding kinase 1 (TBK1), RelA and IFN regulatory factor 3 (IRF3) (Figure 4E).…”
Section: Hervk Expression Triggers the Innate Immune Responsementioning
confidence: 69%